2016
DOI: 10.1097/bco.0000000000000367
|View full text |Cite
|
Sign up to set email alerts
|

Defining the role of bisphosphonates for osteonecrosis of the knee: a systematic review

Abstract: Osteonecrosis of the knee encompasses three conditions: spontaneous, secondary, and postarthroscopic. Treatment options include nonoperative treatment, joint preserving surgery, and arthroplasty. Bisphosphonates have been shown to successfully prevent bone resorption in animal studies and hip osteonecrosis. This article aims to systematically review the available evidence that bisphosphonates reduce pain and improve function in patients with knee osteonecrosis. A systematic review using the online databases Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Oral therapy using bisphosphonates has been recommended in a few case series but concrete evidence of its role in reversing osteonecrosis is yet to be established. 29 A randomized control trial by Meier et al 30 showed no benefits of oral bisphosphonates (ibandronate) over NSAIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Oral therapy using bisphosphonates has been recommended in a few case series but concrete evidence of its role in reversing osteonecrosis is yet to be established. 29 A randomized control trial by Meier et al 30 showed no benefits of oral bisphosphonates (ibandronate) over NSAIDS.…”
Section: Discussionmentioning
confidence: 99%